IMPLEMENTASI SISTEM MONITORING DAN KENDALI GENSET LPG SECARA NEAR REAL-TIME MENGGUNAKAN ESP32-S3 DAN FIREBASE: IMPLEMENTATION OF A NEAR REAL-TIME LPG GENERATOR MONITORING AND CONTROL SYSTEM USING ESP32-S3 AND FIREBASE - Muhammad Arzu Prasetyo; Arya Kusumawardana; Soraya Norma Mustika; Royb Fatkhur Rizal (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
Manual monitoring of generators often leads to delays in detecting malfunctions and is unable to provide near real-time data. This study aims to design and implement an Internet of Things (IoT)-based monitoring and control system for LPG generators using an ESP32-S3 microcontroller integrated with Firebase and an Android application called GENMON (Genset Monitoring System). The system is designed to measure various operational parameters of the generator, including voltage, current, power, temperature, and gas pressure, and to transmit these data continuously to Firebase for display through the Android application. In addition to presenting parameter information, the system is equipped with an automatic notification feature that triggers when abnormal conditions are detected, as well as remote-control functionality for starting and shutting down the generator. This research adopts a practice-based methodology encompassing the design of both hardware and software, followed by system performance testing and application functionality evaluation. Based on the test results, the system demonstrated good performance, with voltage sensor accuracy reaching 98.5%, frequency sensor accuracy reaching 99.33%, and current sensor accuracy reaching 100%, an average notification delay of 1.76 seconds, data transmission latency ±1 second, data synchronization success rate of 90%, and a control response time ranging from 1 to 2 seconds.